2003
DOI: 10.1002/jbt.10068
|View full text |Cite
|
Sign up to set email alerts
|

Signal transduction events in lung injury induced by 2‐chloroethyl ethyl sulfide, a mustard analog

Abstract: Sulfur mustard has been used as a vesicant chemical warfare agent. To understand the mechanism by which mustard gas exposure causes respiratory damage, we have used 2-chloroethyl ethyl sulfide (CEES) as a mustard analog. Our initial studies have shown that guinea pigs exposed to CEES intratracheally accumulate high levels of TNF-alpha. Accumulation of TNF-alpha leads to activation of both acid and neutral sphingomyelinases, resulting in high accumulation of ceramides, a second messenger involved in cell apopto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 40 publications
2
47
1
Order By: Relevance
“…Recent studies indicated that within 30 min of the mustard gas exposure, induction of tumor necrosis factor ␣ (TNF-␣) occurs that initiates a series of signaling events leading to apoptosis [19][20][21]. Inhibition of the initiation of signaling events has not been previously demonstrated.…”
Section: Introductionmentioning
confidence: 96%
“…Recent studies indicated that within 30 min of the mustard gas exposure, induction of tumor necrosis factor ␣ (TNF-␣) occurs that initiates a series of signaling events leading to apoptosis [19][20][21]. Inhibition of the initiation of signaling events has not been previously demonstrated.…”
Section: Introductionmentioning
confidence: 96%
“…Our laboratory has developed a guinea pig model of mustard gas exposure used to study the induction of lung toxicity by 2-chloroethyl ethyl sulfide (CEES), a mustard gas analog. Inhalation of CEES is known to cause hemorrhagic inflammation of the tracheobronchial tree in addition to severe pulmonary complications such as adult respiratory distress syndrome [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Signal transduction has also been demonstrated for CEES, wherein TNF-alpha, sphingomyelinase levels, caspase 3, 8, and 9 were all elevated [10]. Stone et al [5] have found that inflammatory cytokines exacerbate the toxicity of CEES.…”
Section: Mechanism Of Cees/hd-induced Skin Damagementioning
confidence: 99%